Explicating women and their emotional intelligence at workplace (Wisma Wanita) / Nur Fazilah Alidin... [et al.] - Alidin, Nur Fazilah; Berson, Pindatun (2011)
According to Goleman, 1998, Emotional Intelligence can be accept as the capacity for recognizing our own feelings and those for motivating ourselves, and for managing emotions well in ourselves and in our relationships. This form of intelligence is confronted with the purely intellectual intelligence, the one learned at the school, the purely cognitive capabilities measured by IQ tests. Nowadays, we see that many of women involve in working environment where they also sits in high positions like manager, supervisor and administrator. They need the good emotional intelligence because they have to control their work and maintaining the growth of healthy family. Emotional intelligence can be measured by two categories of skills whereas personal skill, focus in how to manage ourselves and the other one is social skills in how to manage other people. This study is to study the understanding on emotional intelligence that effect women in controlling their selves and their subordinate also to look whether women emotional intelligence can relate to their life control and monitor in career and family relationship.